Mechanical-sensorless induction motor drive based only on DC-Link measurements - Sonnaillon, Maximiliano Osvaldo (2006)
Sensor count reduction for high-performance induction motor (IM) drives is considered. A novel strategy to compute the three phase currents, based on a single current sensor and an adaptive observer, is proposed. The observer estimates the motor state variables, allowing then implementing an IM field-oriented controlled (FOC) drive with closed speed loop based only on DC-link measurements. To demonstrate the practical feasibility of this proposal, representative experimental results, obtained with a FOC experimental prototype, are presented. The FOC prototype showed results similar to those from a conventional FOC drive with individual phase current sensors. The sensor count reduction achieved represents a significant cost diminution in the implementation of low-power high-performance drives.